JAK2V617F Is a Risk Factor for TIA/Stroke in Young Patients - Shapira Cohen, Tamar; Chodick, Gabriel; Steinberg, David M.; Grossman, Ehud; Shohat, Mordechai; Salomon, Ophira (Thrombosis and Haemostasis, 2022)
The objective of this study was to assess the risk of arterial thrombosis in patients who harbor the JAK2V617F allele burden ≥1% detected during workup for myeloproliferative neoplasms (MPNs). We conducted a large cross-sectional analysis consisted of 5,220 patients who were tested for JAK2V617F and 1,047,258 people matched in age from health care insurance provider, taking into account age, sex, hypertension, diabetes, atrial fibrillation. Compared with noncarriers, mutation carriers were older, less likely to be current or past smokers and had lower body mass index. There was no significant difference between the groups regarding myocardial infarction and peripheral vascular disease. However, JAK2V617F ≥1% at age 34 to 54 years was associated with eightfold more likely to have transient ischemic attack (TIA)/stroke history unrelated to hypertension, diabetes, or atrial fibrillation. Association of JAK2V617F with TIA/stroke was also observed in the older age group, albeit a weaker association and not statistically significant. Prevalence of TIA/stroke was higher in patients with JAK2V617F negative, with odds ratio of 3.93 when compared with the general population after confounder adjustments. Further research is warranted to verify the relation between allele burden of JAK2V617F mutation and TIA/stroke and the role of JAK2V617F per se as a risk factor for arterial thrombosis in the absence of overt MPN. Also, consideration should be paid to the screened group with JAK2V617F negative due to the high incidence of TIA/stroke among them in comparison to the general population.
Keywords: JAK2V617F; ET; PV; transient ischemic attack; stroke